Fake News and Hate Speech in Nigeria’s Development and Security Trajectory: A Qualitative Assessment - Liadi, Olusegun Fariudeen; Lawal, Musediq Olufemi; Akinrinde, Olawale Olufemi (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
The proliferation of false news and hate speech in Nigeria is posing a severe barrier to information sharing. The ease with which people now propagate destructive views across numerous social platforms complicates the situation even further. Despite multiple studies on the subject in Nigeria, what drives the spread of false news and hate speech and how it affects the country’s security and prosperity remain elusive in the existing literature. This study, therefore, seeks to address that vacuum by delving deeply into the complex dynamics behind these concerns in Nigeria and investigating how they influence the country’s security and prosperity. To grasp the entire scale of false news and hate speech, this study conducted extensive research that included reviewing old documents and conducting in-depth interviews with a varied range of people. The findings of this study indicated that young people are more exposed to the negative consequences of false news and hate speech. The pull of social media and its active debates frequently draws children into situations where they are more likely to encounter incorrect and nasty remarks. Recognizing youth as a significant demographic affected by this issue is critical. It implies that the government must take specific action to address the underlying causes and repercussions of false news and hate speech in Nigeria. This study, as a result, emphasizes the critical necessity for proactive actions to defend Nigeria’s news and information-sharing procedures and platforms. Policymakers may aid Nigerian society by enacting legislation and protections to prevent the detrimental impact of fake news and hate speech. Ultimately, these initiatives can result in a more educated and inclusive public discussion.